Math

posted by .

A ⊆ B. Prove P(A|B)>= P(A)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. geometry

    Given the following sets, select the statement below that is NOT true. A = {b, l, a, z, e, r}, B = {b, a, l, e}, C = {a, b, l, e}, D = {l, a, b}, E = {a, b, l} (Points : 2) E ⊂ C C ⊆ B D ⊆ C B ⊆ C C ⊆ …
  2. discrete math help please

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  3. discrete math help please

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  4. math

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  5. math help

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  6. URGENT! discrete math help please

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  7. URGENT HELP WITH DISCRETE MATH PLEASE

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  8. math. Somebody help urgently please

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  9. math

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
  10. math

    1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …

More Similar Questions